Religious Affections Jonathan Edwards dan Relevansinya bagi Ibadah Komunal - Lucky Samuel (Veritas : Jurnal Teologi dan Pelayanan, 2017)
This article attempts to discuss one of the important writings of Jonathan Edwards, A Treatise Concerning Religious Affections, and its contribution to corporate worship. Since this work has been helpful in evaluating one’s spirituality and in formulating what the authentic spirituality is, this treatise can be also useful in evaluating and designing corporate worship. Focusing on the first three signs of gracious affections according to Edwards, this paper suggests that this treatise can serve as an antidote for three distorted notions in corporate worship, namely legalistic, narcissistic, and therapeutic worship.